Effects of ERβ and ERα on OVX-induced changes in adiposity and insulin resistance. Issue 1 (April 2020) - Zidon, Terese M; Padilla, Jaume; Fritsche, Kevin L; Welly, Rebecca J; McCabe, Leighton T; Stricklin, Olivia E; Frank, Aaron; Park, Youngmin; Clegg, Deborah J; Lubahn, Dennis B; Kanaley, Jill A; Vieira-Potter, Victoria J
Abstract : Loss of ovarian hormones leads to increased adiposity and insulin resistance (IR), increasing the risk for cardiovascular and metabolic diseases. The purpose of this study was to investigate whether the molecular mechanism behind the adverse systemic and adipose tissue-specific metabolic effects of ovariectomy requires loss of signaling through estrogen receptor alpha (ERα) or estrogen receptor β (ERβ). We examined ovariectomized (OVX) and ovary-intactwild-type (WT), ERα-null (αKO), and ERβ-null (βKO) female mice (age ~49 weeks; n  = 7–12/group). All mice were fed a phytoestrogen-free diet (<15 mg/kg) and either remained ovary-intact (INT) or were OVX and followed for 12 weeks. Body composition, energy expenditure, glucose tolerance, and adipose tissue gene and protein expression were analyzed. INT αKO were ~25% fatter with reduced energy expenditure compared to age-matched INT WT controls and βKO mice (all P  < 0.001). Following OVX, αKO mice did not increase adiposity or experience a further increase in IR, unlike WT and βKO, suggesting that loss of signaling through ERα mediates OVX-induced metabolic dysfunction. In fact, OVX in αKO mice (i.e., signaling through ERβ in the absence of ERα) resulted in reduced adiposity, adipocyte size, and IR ( P  < 0.05 for all). βKO mice responded adversely to OVX in terms of increased adiposity and development of IR. Together, these findings challenge the paradigm that ERα mediates metabolic protection over ERβ in all settings. These findings lead us to suggest that, following ovarian hormone loss, ERβ may mediate protective metabolic benefits.